Analisis Sosiologi Hukum Islam terhadap Ketentuan Batas Usia Perkawinan dalam Undang-Undang Nomor 16 Tahun 2019 - oktaviani, Dina; Irwansyah, Shindu; Rojak, Encep Abdul (UNISBA Press, 2025)
Abstract. This study analyzes the implementation of Law No. 16 of 2019 regarding the change in minimum marriage age in Sukagalih Village, Garut Regency, through the perspective of Islamic legal sociology. Using a qualitative juridical-sociological approach with in-depth interviews, participant observation, and literature study methods. The research findings indicate that the socio-cultural conditions of the community, dominated by traditional Sundanese values and classical Islamic understanding, create resistance to regulatory changes. The community shows three response patterns: acceptive (32%), resistant (45%), and adaptive (23%). The normative conflict between positive law and social norms manifests in a 40% increase in marriage dispensation applications and unregistered marriage practices. Maqashid syariah analysis supports the increase in marriage age for child protection and education. Effective implementation requires reinterpretation of religious understanding by involving religious leaders as mediators. Although there was a 25% decrease in early marriage rates, structural barriers in the form of traditional value systems and limited access to information remain significant. Gradual transformation occurs with religious leaders beginning to integrate reproductive health aspects into traditional Islamic understanding. Abstrak. Penelitian ini menganalisis implementasi UU No. 16 Tahun 2019 tentang perubahan batas usia minimal perkawinan di Kampung Sukagalih, Kabupaten Garut, melalui perspektif sosiologi hukum Islam. Menggunakan pendekatan kualitatif yuridis-sosiologis dengan metode wawancara mendalam, observasi partisipan, dan studi pustaka. Hasil penelitian menunjukkan bahwa kondisi sosio-budaya masyarakat yang didominasi nilai tradisional Sunda dan pemahaman Islam klasik menciptakan resistensi terhadap perubahan regulasi. Masyarakat menunjukkan tiga pola respons: akseptif (32%), resisten (45%), dan adaptatif (23%). Konflik norma antara hukum positif dengan norma sosial bermanifestasi dalam peningkatan permohonan dispensasi perkawinan sebesar 40% dan praktik perkawinan tidak tercatat. Analisis maqashid syariah mendukung kenaikan batas usia perkawinan untuk perlindungan anak dan pendidikan. Implementasi efektif memerlukan reinterpretasi pemahaman keagamaan dengan melibatkan tokoh agama sebagai mediator. Meskipun terjadi penurunan angka perkawinan usia muda sebesar 25%, hambatan struktural berupa sistem nilai tradisional dan keterbatasan akses informasi masih signifikan. Transformasi gradual terjadi dengan tokoh agama mulai mengintegrasikan aspek kesehatan reproduksi dalam pemahaman Islam tradisional.